GANESHA SEBAGAI SIMBOL PARADIGMA POSITIVISME - Hari Harsananda; Acyutananda Wayan Gaduh (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Positivism is a philosophical paradigm that contributes greatly to the development of science in the world, with many types of philosophical thinking in the realm of thought, it is deemed necessary to carry out the paradigm. paradigm serves to help distinguish one scientific community with other scientific communities There are many sciences that were born from the philosophy of positivism such as mathematics, physics and other natural sciences. This knowledge can be categorized as hard science that formulates problems outside of human beings. The existence of positivism is always attached to western philosophy which is considered as the forerunner to philosophy, but the positivism paradigm is actually present also in the local scientific dimension, namely Paradigm Ganesha as a god for posivistic sciences.